2020
DOI: 10.1128/jb.00618-19
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Zinc Impacts Interactions between Streptococcus sanguinis and Pseudomonas aeruginosa in Coculture

Abstract: Airway infections associated with cystic fibrosis (CF) are polymicrobial. We reported previously that clinical isolates of Pseudomonas aeruginosa promote the growth of a variety of streptococcal species. To explore the mechanistic basis of this interaction, we performed a genetic screen to identify mutants of Streptococcus sanginuis SK36 whose growth was no longer enhanced by P. aeruginosa PAO1. Mutations in the zinc uptake systems of S. sanguinis SK36 reduced growth of these strains by 1 to 3 logs compared to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 80 publications
1
16
0
Order By: Relevance
“…Smith et al (1) found that the zinc concentration of 45 CF sputum samples ranged from 678 μg/L (~10 μM) to 1181 μg/L (~18 μM) compared to 103 μg/L (~2 μM) to 597 μg/L (~9 μM) in 8 non-CF sputum samples. Li et al (3) reported that the zinc concentration of 118 CF sputum samples ranged from ~5 μM to ~145 μM. In this study, the zinc concentration of 8 CF sputum samples ranged from 1.002 μg/g (~15 μM) to 7.562 μg/g (~116 μM) ( Fig.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Smith et al (1) found that the zinc concentration of 45 CF sputum samples ranged from 678 μg/L (~10 μM) to 1181 μg/L (~18 μM) compared to 103 μg/L (~2 μM) to 597 μg/L (~9 μM) in 8 non-CF sputum samples. Li et al (3) reported that the zinc concentration of 118 CF sputum samples ranged from ~5 μM to ~145 μM. In this study, the zinc concentration of 8 CF sputum samples ranged from 1.002 μg/g (~15 μM) to 7.562 μg/g (~116 μM) ( Fig.…”
Section: Discussionmentioning
confidence: 49%
“…While the concentration of metals, such as zinc, in CF sputum can vary, the concentration of zinc in expectorated sputum from CF patients is elevated, on average, compared to levels in samples from healthy controls (1)(2)(3). However, studies investigating the transcriptional response of P. aeruginosa in CF sputum show that a common gene expression pattern is the increased expression of zinc uptake and transport genes (4)(5)(6)(7)(8)(9), which are normally expressed when zinc is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Our data indicated that C. violaceum requires the ZnuABC system to supply zinc to several physiological processes, such as violacein production, swimming motility, biofilm formation, and bacterial competition. It has been described the requirement of zinc for enzymes of the violacein biosynthetic pathway in C. violaceum (45), for flagellar motility in Proteus mirabilis, S. Typhimurium, and P. aeruginosa (46)(47)(48), for biofilm formation via surface adhesion proteins in Staphylococcus epidermidis and Staphylococcus aureus (49), and for bacterial competition in a context of polymicrobial infections (19,50). Although further studies are needed to understand how these processes were impaired under zinc deficiency in C. violaceum, our data suggest an adaptive response to ensure the zinc supply for key metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have focused on the metabolic interactions of microbes found in the CF airway, most of them have included two microbial species due to complex experimental methods required to culture multiple microbes in a mixed community in vitro ( Filkins et al, 2015 ; Flynn et al, 2016 ; Scott et al, 2019 ; Camus et al, 2020 ; Li et al, 2020 ). However, metabolic modeling represents a useful tool to interrogate metabolic dependencies of more complex multispecies communities detected in pwCF.…”
Section: Introductionmentioning
confidence: 99%